Analisis Peran Guru Sebagai Motivator Pada Pembelajaran IPS Siswa Kelas Tinggi Dalam Pembelajaran Daring - Nurafrianti, Siti Sahla; Amalia, Arsyi Rizqia; Nurasiah, Iis (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to analyze the role of the teacher and the obstacles faced when the teacher becomes a motivator for high-grade students social studies learning in online learning. This research was conducted at SDN Cipanengah CBM Sukabumi, which counted from May to July. This research uses descriptive qualitative research methods. The subjects used in this study were teacher of class 5.3 and students of class 5.3 at SDN Cipanengah CBM. Data collection techniques used in this study in the form of open questionnaires, semi-structured interviews, and documentation. The result of this study is the role played by the teacher during a motivator in high-grade students social studies learning, among other, to encourage students, giving praise, carrying out interesting learning, assigning tasks that are competent among students and there is good cooperation between students and teacher in creating learning active and conducive learning. There are obstacles when the teacher motivates online social studies learning from internal factors that originate from within students and external factors that come from outside themselves such as the family environment.